Immature Follicular Origins and Disrupted Oocyte Growth Pathways Contribute to Decreased Gamete Quality During Reproductive Juvenescence in Mice - Kusuhara, Atsuko; Babayev, Elnur; Zhou, Luhan T.; Singh, Vijay P.; Gerton, Jennifer L.; Duncan, Francesca E. (Frontiers in Cell and Developmental Biology, 2021)
Egg quality dictates fertility outcomes, and although there is a well-documented decline with advanced reproductive age, how it changes during puberty is less understood. Such knowledge is critical, since advances in Assisted Reproductive Technologies are enabling pre- and peri-pubertal patients to preserve fertility in the medical setting. Therefore, we investigated egg quality parameters in a mouse model of the pubertal transition or juvenescence (postnatal day; PND 11-40). Animal weight, vaginal opening, serum inhibin B levels, oocyte yield, oocyte diameter, and zona pellucida thickness increased with age. After PND 15, there was an age-associated ability of oocytes to resume meiosis and reach metaphase of meiosis II (MII) following in vitro maturation (IVM). However, eggs from the younger cohort (PND 16-20) had significantly more chromosome configuration abnormalities relative to the older cohorts and many were at telophase I instead of MII, indicative of a cell cycle delay. Oocytes from the youngest mouse cohorts originated from the smallest antral follicles with the fewest cumulus layers per oocyte, suggesting a more developmentally immature state. RNA Seq analysis of oocytes from mice at distinct ages revealed that the genes involved in cellular growth signaling pathways (PI3K, mTOR, and Hippo) were consistently repressed with meiotic competence, whereas genes involved in cellular communication were upregulated in oocytes with age. Taken together, these data demonstrate that gametes harvested during the pubertal transition have low meiotic maturation potential and derive from immature follicular origins.